Draft Genome Sequences of Two Thermotolerant Cyanobacterial Strains Isolated from Hot Springs - Mironov, Kirill S.; Sinetova, Maria A.; Kupriyanova, Elena V.; Ustinova, Vera V.; Kozlova, Anna Y.; Messineva, Ekaterina M.; Gabrielyan, David A.; Bedbenov, Vladimir S.; Zayadan, Bolatkhan K.; Los, Dmitry A. (Genome announcements (Washington, DC), 2018)
We report here two draft cyanobacterial genome sequences, those of Cyanobacterium aponinum IPPAS B-1201, isolated from a hot spring in the Turgen Gorge (Kazakhstan), and the uncharacterized cyanobacterium IPPAS B - 1203, isolated from a hot spring in Karlovy Vary (Czech Republic). These two strains were deposited at the Collection of Microalgae (IPPAS) of the Timiryazev Institute of Plant Physiology.